2325. Bloodstream Infections in Hospitalized Children in the United States: Incidence, Pathogens, and Regional Differences. (26th November 2018) - Spaulding, Alicen B; Watson, Dave; Dreyfus, Jill; Bendel-Stenzel, Ellen; Heaton, Phillip; Grapentine, Steve; Kharbanda, Anupam
Abstract: Background: Bloodstream infections (BSI) cause significant morbidity and mortality in children, leading to longer hospital stays and increased healthcare costs. Recent epidemiology on national trends and pathogens in children is lacking, which could improve prevention strategies and empiric therapy selection. Methods: We conducted a retrospective cohort study utilizing demographic and microbiology data from the Premier Healthcare Database, including all inpatient encounters from 2009–2016 among patients <19 years. BSI were identified via a documented positive blood culture; known contaminants were excluded. Incidence rate was the number of BSI-positive patient encounters per 10, 000 admissions. Demographics were analyzed comparing BSI-positive to patients without a documented positive BSI (non-BSI). Hospital-acquired infections were defined as those occurring at least 2 days after admission and analyzed only for non-neonates. Differences were assessed using chi-square tests and t-tests; time trends were analyzed using Cochran-Armitage tests. Results: Among 162 US hospitals reporting ≥4 years of blood cultures, 1, 809, 722 patient encounters met inclusion criteria; 6, 152 (0.34%) had a positive BSI. BSI patients were significantly more often 1–5 years old (16% vs. 6%), and had a complex chronic condition (26% vs. 5%), central line (34% vs. 2%), or catheter (12% vs. 3%) compared with non-BSI patients. Overall BSI incidence rate declined over time (37.0 in 2009 vs. 31.9 in 2016 per 10, 000 admissions, P < 0.001). Among non-neonates, pathogens with the highest incidence rates (per 10, 000 admissions) were methicillin-susceptible Staphylococcus aureus (MSSA) (10.5), E. coli (10.4), and Streptococcus pneumoniae (6.4); among neonates incidence was highest for E. coli (4.3), Group B Streptococcus (4.0) and MSSA (2.6). Incidence increased significantly over time in two US regions while decreasing in three (Figure 2). Conclusion: Hospitalized children remain at risk of community and hospital-acquired BSI. Due to substantial efforts, pediatric BSI incidence has declined nationally in recent years. However, more effective methods to prevent and assess patients at risk for BSI are warranted. Disclosures: J. Dreyfus, Premier, Inc.: Employee and Shareholder, Salary.